International consensus recommendations on the management of people with haemophilia B. (April 2022) - Hart, Daniel P.; Matino, Davide; Astermark, Jan; Dolan, Gerard; d'Oiron, Roseline; Hermans, Cédric; Jiménez-Yuste, Victor; Linares, Adriana; Matsushita, Tadashi; McRae, Simon; Ozelo, Margareth C.; Platton, Sean; et al.
Haemophilia B is a rare X-linked genetic deficiency of coagulation factor IX (FIX) that, if untreated, can cause recurrent and disabling bleeding, potentially leading to severe arthropathy and/or life-threatening haemorrhage. Recent decades have brought significant improvements in haemophilia B management, including the advent of recombinant FIX and extended half-life FIX. This therapeutic landscape continues to evolve with several non-factor replacement therapies and gene therapies under investigation. Given the rarity of haemophilia B, the evidence base and clinical experience on which to establish clinical guidelines are relatively sparse and are further challenged by features that are distinct from haemophilia A, precluding extrapolation of existing haemophilia A guidelines. Due to the paucity of formal haemophilia B-specific clinical guidance, an international Author Group was convened to develop a clinical practice framework. The group comprised 15 haematology specialists from Europe, Australia, Japan, Latin America and North America, covering adult and paediatric haematology, laboratory medicine and biomedical science. A hybrid approach combining a systematic review of haemophilia B literature with discussion of clinical experience utilized a modified Delphi format to develop a comprehensive set of clinical recommendations. This approach resulted in 29 recommendations for the clinical management of haemophilia B across five topics, including product treatment choice, therapeutic agent laboratory monitoring, pharmacokinetics considerations, inhibitor management and preparing for gene therapy. It is anticipated that this clinical practice framework will complement existing guidelines in the management of people with haemophilia B in routine clinical practice and could be adapted and applied across different regions and countries.